Influencia de la Temperatura en la Floración del Algarrobo (Prosopis pallida) en los valles: Bajo Piura, Chira. Región Piura-Perú - Dedios Mimbela, Ninell (2018)
This study refers to the methodology process applied included the results achieved and recommendations as temperature and its variability influence the flowering process of algarrobo. The collection of studies on algarrobo (Prosopis pallida) are important and necessary to understand the biophysical scenario in which the process develops and adaptability to climate variability. The overall objective of the study focuses on assessing the influence of temperature on the flowering phase of Prosopis pallida (algarrobo) in Mallares, Bernal and La Esperanza studies sector. We found a positive correlation between the advancement of the bloom with abundant flowers in relation to the behavior of the temperature and how they influence the sectors Niño 1 +2 and Niño 3.4 on the variability of the temperature and turn on the advancement and / or abundance of this phase. In the present study we observed that flowering is not stable both seasonally and annually but varies from year to year as studies indicated by FAO and some authors.